Застосування структурних підходів до розв’язання задач аналізу та прогнозування поведінки екологічних неперіодичних процесів геологічної природи - Selin, Yu. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
One of the possible variants of the solution to problems of analysis and forecasting the behavior of nonperiodic ecological processes of geological nature is presented. It is based on the structural approaches used in the modified similar trajectories technique. An example of using this method for the solution of practical problems of forecasting ecological processes of geological nature is described.